Drug promotional literature: Does pharmaceutical industry follow WHO guidelines? - Sonwane, Priyanka G.; Karve, Ashwini V. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Promotional literature is an important tool for both pharmaceutical industry (marketing strategy) and physicians (up to date knowledge). Important ways of doing drug promotion are visual aids, leave behind, flip charts. World Health Organisation has laid down criteria for drug promotional literature. Methods: A cross sectional observational study was performed in Department of Pharmacology, Tertiary Care Teaching Hospital of Mumbai. Total 137 drug promotional Literatures were randomly collected from different outpatient departments out of which 37 were excluded. 100 drug promotional literatures were evaluated by using WHO guidelines. Results: None of drug promotional literature fulfilled all WHO criteria. Though name of the active ingredient and brand name featured in 100% of the literature, 69% of them lacked information related to adverse drug reactions, precautions, contraindications and warnings. The approved therapeutic uses were mentioned in 96% but the dosage regimen in 38% only. Majority of the literature (80%) did not mention the drug interactions. References were given in 76% of the literature of which 87% were from journal article. Conclusions: Pharmaceutical industries do not follow WHO guidelines in toto to promote their product. Thus more strict regulations need to be implemented for proper promotion and dissemination of information about new drugs.